The abstraction of labour from the factory to the platform: charting the visual language of automation - Tsvetelina Hristova (Work Organisation, Labour and Globalisation)
In this article, I argue that the entanglements between visuality and automation need to be situated and analysed as part of the abstraction of labour and the labour process in capitalism. The striving to standardise, control and optimise the labour process is the original drive behind the operationalisations of visuality in service of capitalist industrial technology. This includes contemporary AI systems, which, despite their increasing complexity, can and should be traced back to the division of labour ( Pasquinelli, 2023 ). My work focuses on the process diagram and its uses in low-code and no-code tools for robotic process automation (RPA), where it is instrumentalised as a form of labour abstraction for the automation of white-collar work. I show how visuality can help us trace the transformation between the techniques of labour abstraction in early scientific management, on the one hand, and data and algorithms as a particular type of abstract labour, on the other hand. Building on Jathan Sadowski’s (2019) point that data is manufactured through the agency of labour as a ‘recorded abstraction of the world created and valorised by people using technology’ (ibid.:2), I argue that the process diagram serves as a vantage point through which this process of abstraction and the role of visuality in enabling and obscuring this process can be investigated.